Nordsieck methods with inherent quadratic stability - Braś, M. (Mathematical Modelling and Analysis, 2011)
We derive suffcient conditions which guarantee that the stability polynomial of Nordsieck method for ordinary differential equations has only two nonzero roots. Examples of such methods up to order four are presented which are A-and L-stable. These examples were obtained by computer search using the Schurcriterion applied to the quadratic factor of the resulting stability polynomials.